Nutritional, Physical and Microbiological Properties of Gluten Free Bread with Chia Seed Flour as Alternative Thickening Agent - Dina A. Anwar; Sayed A. Soliman; Heba R. Eid; Sayed Rashad (Food Technology Research Journal, 2024)
This study investigated the impact of substituting xanthan gum with chia (Salvia hispanica L.) on the nutritional and microbiological quality of gluten-free pan bread. A gluten-free pan bread base using composite flour made from millet, corn, potato, and chickpea flour was developed. chia seeds were then incorporated at three levels (1%, 2%, and 3%) as a potential replacement for xanthan gum. The composite flour analysis revealed a composition of 8.94% protein, 1.63% fat, 2.15% crude fiber, 3.38% ash, and 83.90% carbohydrate. Gluten-free pan bread samples were analyzed for their nutritional properties and microbiological quality over 12 days of storage (room temperature). Our results indicated that pan bread made with chia was superior in many nutritional aspects compared to the control and the xanthan treatment. Chia inclusion in pan bread significantly increased protein, fat, fiber, and minerals like iron, calcium, zinc, and potassium. In all gluten-free pan bread samples and the composite flour, the content of insoluble dietary fiber (IDF) was higher than soluble dietary fiber (SDF). Compared to the control and 2% xanthan samples, adding chia increased the levels of most essential amino acids (isoleucine, lysine, cystine, methionine, threonine, and valine) and most fatty acids. Microbiological analysis indicated that chia inclusion improved the shelf-life of the gluten-free pan bread by protecting it from microbial spoilage. Overall, chia seeds demonstrate promise as a thickening ingredient for gluten-free pan bread, offering significant nutritional benefits and improved shelf life.